Domino and Leaflet Media: Efforts to Improve Adolescents’ Knowledge about Premarital Sex - Kustin; Ico Bayu Dewangkoro (Al-Hijrah Indonesia, 2026)
Several issues faced by adolescents today include a lack of knowledge about sexual health, with most adolescents still unaware of the dangers of premarital sex, which can lead to unwanted pregnancies. The aim of this study was to determine the effect of the domino game media on adolescents’ knowledge regarding premarital sex. This study employed a quantitative approach using a quasi-experimental method with a two-group pretest and posttest design. The sampling technique used was non-probability sampling with a purposive sampling approach. The total sample consisted of 64 respondents, divided into 32 participants in the control group and 32 in the intervention group, who were given the domino game at SMK 4 Pancasila Ambulu. Data were analyzed univariately using the Wilcoxon test and bivariately using the Mann–Whitney test with SPSS software. The Wilcoxon test results showed significant differences between the pretest and posttest in both the intervention and control groups, with a p-value of 0.001 (<0.05). Similarly, the Mann–Whitney test also indicated a significant result with a p-value of 0.001 (<0.05). Therefore, it can be concluded that the use of the domino game as an educational medium significantly influenced adolescents’ knowledge about premarital sex. The domino game proved to be a useful learning tool, as the findings showed a marked improvement in adolescents’ knowledge after the intervention compared to before.